Genotype–phenotype relationship and risk stratification in loss‐of‐function SCN5A mutation carriers. Issue 5 (30th April 2018) - Robyns, Tomas; Nuyens, Dieter; Vandenberk, Bert; Kuiperi, Cuno; Corveleyn, Anniek; Breckpot, Jeroen; Garweg, Christophe; Ector, Joris; Willems, Rik
Abstract : Introduction: Loss‐of‐function (LoF) mutations in the SCN5A gene cause multiple phenotypes including Brugada Syndrome (BrS) and a diffuse cardiac conduction defect. Markers of increased risk for sudden cardiac death (SCD) in LoF SCN5A mutation carriers are ill defined. We hypothesized that late potentials and fragmented QRS would be more prevalent in SCN5A mutation carriers compared to SCN5A ‐negative BrS patients and evaluated risk markers for SCD in SCN5A mutation carriers. Methods: We included all SCN5A loss‐of‐function mutation carriers and SCN5A ‐negative BrS patients from our center. A combined arrhythmic endpoint was defined as appropriate ICD shock or SCD. Results: Late potentials were more prevalent in 79 SCN5A mutation carriers compared to 39 SCN5A ‐negative BrS patients (66% versus 44%, p  =   .021), while there was no difference in the prevalence of fragmented QRS. PR interval prolongation was the only parameter that predicted the presence of a SCN5A mutation in BrS (OR 1.08; p  <   .001). Four SCN5A mutation carriers, of whom three did not have a diagnostic type 1 ECG either spontaneously or after provocation with a sodium channel blocker, reached the combined arrhythmic endpoint during a follow‐up of 44 ± 52 months resulting in an annual incidence rate of 1.37%. Conclusion: LP were more frequently observed in SCN5A mutation carriers, while fQRS was not. In SCN5A mutation carriers, the annual incidence rate of SCD was non‐negligible, even in the absence of a spontaneous or induced type 1 ECG. Therefore, proper follow‐up of SCN5A mutation carriers without Brugada syndrome phenotype is warranted.